Avoidable causes on the waiting list for admissions to intensive care units - Guido Luis Gomes Otto; Marielle Priscila de Paula Silva; Cássia Kely Favoreto Costa; Marcelo Picinin Bernuci; Mirian Ueda Yamaguchi (Rev Rene, 2016)
Objective: to evaluate occurrence of avoidable-mortality causes on the waiting list of patients at the intensive care units. Methods: one thousand, two hundred and twelve enrollments of patients from all age groups were analyzed and classified according to the Brazilian Health System for causes of avoidable mortality. Descriptive statistics for simple, relative and mean frequency rates were employed for the comparative analysis of the variables. Results: cases of non-communicable diseases, among the avoidable-mortality causes, occupied more than 80.0% of intensive care unit´s beds. Hospitalizations comprised illnesses of the circulatory and respiratory apparatus, especially in patients over 40 years old, together with the external causes and consequences of pregnancy and puerperium with mortality rates within the 15-39 age group. Conclusion: the high proportion of patients with diseases from avoidable causes on the waiting list for intensive care units hospitalization suggest that improvements in the programs involved with the prevention of diseases, especially non-communicable diseases, are needed.